Evidence-based practice and knowledge utilisation – a study of attitudes and practices among social workers in Germany. Issue 5 (3rd September 2019) - James, Sigrid; Lampe, Leoni; Behnken, Susan; Schulz, Daniel
ABSTRACT: This study aimed to add to the limited empirical knowledge base on evidence-based practice (EBP) and social work in Germany. Using a regional sample of 158 social workers that were recruited through stratified sampling procedures, the study examined knowledge utilisation as well as attitudes toward the use of research-based practice methods, administering a normed and internationally recognised instrument, the Evidence-Based Practice Attitude Scale (EBPAS). It further examined practitioner-level predictors of openness toward research-based methods. Findings indicated limited familiarity with the concept of EBP and showed that research and theory were not primary sources of knowledge to guide practice. Yet, attitudes toward research-based methods were overall positive and indicated considerable openness if methods made sense, were appealing, and sufficient training and support were provided. Scepticism and negative attitudes were evident in some areas (e.g. manualization, requirements). Multivariate linear regression indicated that individuals in leadership positions held more positive attitudes while a longer job tenure was inversely related to openness, approaching significance. Findings of the study are compared to the U.S. normative sample as well as a prior German study using the EBPAS. Implications for knowledge development in the discipline of social work in Germany are discussed.